Parent-child neural similarity: Measurements, antecedents, and consequences - Qu, Yang; Zhou, Zexi; Lee, Tae-Ho (Frontiers in Cognition, 2023)
Children and their parents are wired to connect as it provides the foundation for developing children to adapt to an increasingly complex environment. Although extensive studies demonstrate the importance of parent-child dyadic similarity at the behavioral, psychological, and physiological levels in fostering children’s learning and psychological well-being, little is known about parent-child similarity at the neural level until recently. Drawing on our own work and the work by other scholars, this review summarizes recent advances in empirical research on parent-child neural similarity. Specifically, this review elaborates the theoretical importance of studying parent-child neural similarity and showcases how parent-child neural similarity is assessed using different neuroimaging approaches. We further synthesize empirical evidence about the contextual and individual factors that may contribute to variability in parent-child neural similarity, summarize how such neural similarity is related to different aspects of child adjustment, and highlight important directions for future research. Taken together, we hope that this integrative review can demonstrate cutting-edge research that explore neural similarity in parent-child dyads, and provide researchers with a clear roadmap to examine parent-child neural similarity in order to gain a better understanding of parental socialization process and brain development.